Giant Humidity Response Using a Chitosan-Based Protonic Conductive Sensor - Zou, Jianping (2017)
As a natural biopolymer, chitosan has a very unique protonic conductivity that is highly sensitive to water vapor. However, there has been no report on pure chitosan-based resistive humidity sensors, probably due to the difficulty of direct-current measurement of protonic current in chitosan. Here, a simple and cost-effective chitosan-based protonic conductive humidity sensor is presented. The sensor exhibits a large conductance response of four orders of magnitude when relative humidity is increased from 10% up to 90%. The effects of adsorbed water on proton density and dielectric constant change of chitosan could be responsible for the giant humidity response. More importantly, the sensor shows high stability, repeatability, recoverability, and selectivity to water vapor over ethanol, acetone, and toluene vapors.